-1n+2+3n=-6

Simple and best practice solution for -1n+2+3n=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1n+2+3n=-6 equation:


Simplifying
-1n + 2 + 3n = -6

Reorder the terms:
2 + -1n + 3n = -6

Combine like terms: -1n + 3n = 2n
2 + 2n = -6

Solving
2 + 2n = -6

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 2n = -6 + -2

Combine like terms: 2 + -2 = 0
0 + 2n = -6 + -2
2n = -6 + -2

Combine like terms: -6 + -2 = -8
2n = -8

Divide each side by '2'.
n = -4

Simplifying
n = -4

See similar equations:

| 8x^2+0.9x=0.06 | | 10x-3=18x+17 | | 10x-3=18x+7 | | -4b-3=2b-5 | | 6/x-52=15/x-2 | | 3=3-4n-3n | | y=0.5x^2+4x | | 36x^2+13x-40=0 | | 8-8a=2 | | Y+13=-1[x+3] | | 2-6/3=-5/2 | | -20=-2n-3n-5 | | x^2+tx+3=0 | | 3[2x-y]=9x+12 | | 5=15-2y | | 5/2x=28 | | [y-5]=3[x-2] | | 5p^2-12p=32 | | (y+12)=3(x-9) | | 2=-1n+2n-2 | | -6(2x+4)=-18 | | (x/5)-(y/10)=(7/10) | | 9(x+5)-(4x-1)=8 | | 15+35x= | | 4x+2x-2=6x-3+1 | | -4cosx-3sinx=2 | | 3-n-4n=-2 | | 6t^2+18t+12=0 | | [y-5]=3[x+2] | | 0n+4n+1=17 | | 5(2x-7)=7x+3x+7 | | -5=8f+11 |

Equations solver categories